2004
DOI: 10.1111/j.1349-7006.2004.tb03255.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐associated silencing of the Wnt antagonist SFRP1 gene in human ovarian cancers

Abstract: The SFRP1 gene on chromosome 8p11.2 encodes a Wnt signaling antagonist, and was recently demonstrated to be a new tumor suppressor that is inactivated by promoter methylation in human colon cancers. Here, we analyzed promoter methylation of the SFRP1 gene in human ovarian cancers, in which loss of heterozygosity in 8p is frequently observed and involvement of the Wnt signaling pathway has been suggested. Methylation-specific PCR (MSP) analysis showed that four of 13 ovarian cancer cell lines and two of 17 prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 23 publications
1
73
0
Order By: Relevance
“…We and others have reported that TMS1, 14-3-3sigma and WT1 genes are methylated more frequently in clear cell tumours than in other tumour types (Kaneuchi et al, 2004;Terasawa et al, 2004;Kaneuchi et al, 2005), whereas methylation of SFRP1, 18S and 28S ribosomal DNA genes is more frequently detected in nonclear cell tumours, such as the serous type (Takada et al, 2004;Chan et al, 2005). Although the molecular mechanisms responsible for the differing methylation profiles in different tumour types remains unclear, gene methylation may have relevance in the clinical situation.…”
Section: Discussionmentioning
confidence: 66%
“…We and others have reported that TMS1, 14-3-3sigma and WT1 genes are methylated more frequently in clear cell tumours than in other tumour types (Kaneuchi et al, 2004;Terasawa et al, 2004;Kaneuchi et al, 2005), whereas methylation of SFRP1, 18S and 28S ribosomal DNA genes is more frequently detected in nonclear cell tumours, such as the serous type (Takada et al, 2004;Chan et al, 2005). Although the molecular mechanisms responsible for the differing methylation profiles in different tumour types remains unclear, gene methylation may have relevance in the clinical situation.…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that downregulated expression of APC (Karbova et al, 2002) or secreted frizzled-related proteins (SFRPs) inactivation by methylation (Takada et al, 2004) could explain, at least partially, why ovarian serous adenocarcinomas show increased b-catenin protein expression in spite of the absence of gene mutation. However, none of these studies has shown any statistical correlation between these molecules and subcellular localisation of b-catenin in tissue samples (Karbova et al, 2002;Takada et al, 2004). Whether deregulation of these molecules contributes to the accumulation of b-catenin in ovarian serous adenocarcinomas is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms, however, which initiate and maintain HAND1 expression in extraembryonic cell types are not well known. A role of HAND1 in cell proliferation and neoplastic transformation has been recently envisaged because HAND1 gene has been found silenced and hypermethylated in human gastric (Kaneda et al, 2002), pancreatic (Hagihara et al, 2004) and ovarian carcinomas (Takada et al, 2004).…”
Section: Introductionmentioning
confidence: 99%